Characterization of a newly synthesized fluorescent benzofuran derivative and usage as a selective fiber optic sensor for Fe(III) - Oter, Ozlem; Ertekin, Kadriye; Kirilmis, Cumhur; Koca, Murat; Ahmedzade, Misir (Elsevier Science Sa, 2007)
In this work photoluminescent properties of Fe3+ selective organic fluoroionophore, benzofuran derivative bis(7-methoxybenzofuran-2-il)ketoxime (BFK) was investigated in different solvents (dichloromethane, tetrabydrofuran, toluene and ethanol) and in polymer matrices of polyvinylchloride (PVC) and ethyl cellulose (EC) by absorption and emission spectrometry. The photophysical constants such as quantum yield, Stock's shift and molar extinction coefficient of the BFK dye were declared. The immobilized dye was found to exhibit a selective response for Fe3+ in direction of decrease in fluorescence intensity. The response to Fe3+ ions was evaluated in terms of the effect of pH and cross sensitivity to Fe2+ and other cations. The response time, reversibility, limit of detection, linear concentration range for the metal ion and repeatability characteristics of the sensing reagent also have been studied. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzofuran derivative; iron sensor; Fe3+; fluorescence spectroscopy